2010
DOI: 10.1002/app.31241
|View full text |Cite
|
Sign up to set email alerts
|

Phase separation behavior and morphologies of PMMA/poly(styrene‐co‐acrylonitrile)/clay nanocomposites prepared by solution mixing

Abstract: Nanocomposites of blends of PMMA and poly(styrene-co-acrylonitrile) (SAN) with natural (PM) or organically modified montmorillonite clays (Cloisite 30B, 25A, and 15A) were prepared by solution mixing and the effect of clay on the phase separation behavior along with morphologies of nanocomposites was investigated. Nanocomposites containing clay C30B prepared from methyl ethyl ketone showed the noticeable decrease in the cloud points. None of the other nanocomposites showed the increase in the cloud point. Loca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…26 SAN/PMMA blends show the lower critical solution temperature behavior. [26][27][28][29][30] The phase diagrams of the PMMA/ SAN systems were determined by many methods such as cloud point measurement, laser light scattering and infrared microscopy. 31 Wacharawichanant et al 28 have studied the phase separation of SAN/PMMA blends and found that, from the cloud point temperatures measurements for blends containing SAN copolymers with about 25 wt% of AN, the critical composition should be between 10 and 20 wt% of SAN.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…26 SAN/PMMA blends show the lower critical solution temperature behavior. [26][27][28][29][30] The phase diagrams of the PMMA/ SAN systems were determined by many methods such as cloud point measurement, laser light scattering and infrared microscopy. 31 Wacharawichanant et al 28 have studied the phase separation of SAN/PMMA blends and found that, from the cloud point temperatures measurements for blends containing SAN copolymers with about 25 wt% of AN, the critical composition should be between 10 and 20 wt% of SAN.…”
Section: Introductionmentioning
confidence: 99%
“…26 SAN/PMMA blends show the lower critical solution temperature behavior. 2630 The phase diagrams of the PMMA/SAN systems were determined by many methods such as cloud point measurement, laser light scattering and infrared microscopy. 31 Wacharawichanant et al.…”
Section: Introductionmentioning
confidence: 99%